A relação afetiva entre professores e alunos na transição dos anos iniciais para os anos finais do ensino fundamental - Bôas, Márcia Martins Villas (2014)
This Dissertation intends to search and understand what happens to student's when they change from a multiple subject single teacher to a group of single subject teachers, regarding the motivation to learn, since in teacher's staff meeting this matter always comes up for discussion and apparently students tose focus failing to take account of the vaious themes and activities requested by severa) teachers that tend tu have at this stage and their will to learn. Thus, a search was made in three Porto Alegre schools with two sixth year teachers and two seventh year students each to report their experiente in this transition. The method used was the qualitative research with semistructured interview. The data collected were analized through the methodology of subject analisis according to Bardin (2009), in a qualitative approach agming to interpretate and reinterpret the results, seeking a better comprehension of bh2ir meanings. The teacher's report, as well as the student's, has shown us that at first glance teachers and students are better tuned with each other, understanding and respecting the space that each has within the school community, making it clear tat students can identify that it considers to be a good teacher. The continued icrmation allied with the cate in this transition, by the school staff, made this shift be áed smoothly by both students and teachers which eased the matter of disinterest and disorganization from the students.